Protected area downgrading, downsizing, and degazettement (PADDD) in marine protected areas. (July 2021) - Albrecht, Renee; Cook, Carly N.; Andrews, Olive; Roberts, Kelsey E.; Taylor, Martin F.J.; Mascia, Michael B.; Golden Kroner, Rachel E.
Abstract: Marine protected areas (MPAs) are foundational to global marine biodiversity conservation efforts. Recently, countries have rapidly scaled up their MPA networks to meet targets established by the Convention on Biological Diversity (CBD). While MPA networks are intended to permanently safeguard marine ecosystems, evidence points to widespread legal changes that temper, reduce, or eliminate protected areas, known as protected area downgrading, downsizing, and degazettement (PADDD). Research on PADDD to-date has focused on terrestrial PAs, leaving fundamental questions about PADDD in MPAs unanswered. To address this knowledge gap and provide a foundation for understanding the conservation implications of PADDD in marine ecosystems, we documented patterns, trends, and proximate causes of PADDD in MPAs globally. At least six countries have enacted 43 PADDD events in MPAs, most of which were in Australian MPAs. Globally, PADDD events in MPAs have affected an area of at least 1, 198, 774 square kilometers, approximately the size of South Africa. Most PADDD events in MPAs (79%) are associated with industrial-scale resource use, extraction, and development, suggesting that PADDD may undermine the conservation objectives of MPAs. Additional research, transparency, and proactive policy responses are needed to address PADDD to better safeguard marine ecosystems. Highlights: Protected area downgrading, downsizing, and degazettement (PADDD) affects MPAs. We documented patterns, trends, and causes of enacted and proposed PADDD in MPAs. Widespread downgrading in Australia allowed commercial and recreation fishing. Downgrades to the Coral Sea Marine Park constitute the largest PA downgrade to date. Science and policy responses are required to safeguard MPAs in the long term.